2020
DOI: 10.3389/fimmu.2020.576516
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-155 Is Decreased During Atherosclerosis Regression and Is Increased in Urinary Extracellular Vesicles During Atherosclerosis Progression

Abstract: BackgroundAtherosclerosis is a chronic inflammatory disease driven by macrophage accumulation in medium and large sized arteries. Macrophage polarization and inflammation are governed by microRNAs (miR) that regulate the expression of inflammatory proteins and cholesterol trafficking. Previous transcriptomic analysis led us to hypothesize that miR-155-5p (miR-155) is regulated by conjugated linoleic acid (CLA), a pro-resolving mediator which induces regression of atherosclerosis in vivo. In parallel, as extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…Poor angiogenesis or calcification is also a critical factor worsening the prognosis of diabetic angiopathy. MiR-155-5p is considered to suppress anti-inflammatory signaling in macrophages and participate in the regulation of neovascularization ( 34 , 35 ). Previous studies on miR-155-5p demonstrated a significant down-regulation in peripheral blood mononuclear cells and whole blood from patients with diabetes ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poor angiogenesis or calcification is also a critical factor worsening the prognosis of diabetic angiopathy. MiR-155-5p is considered to suppress anti-inflammatory signaling in macrophages and participate in the regulation of neovascularization ( 34 , 35 ). Previous studies on miR-155-5p demonstrated a significant down-regulation in peripheral blood mononuclear cells and whole blood from patients with diabetes ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of miR-155 are found during the reversion of atherosclerosis in vivo . Furthermore, miR-155 is found in high concentrations in urinary EVs in patients with unstable coronary artery disease ( 82 ). Moreover, Zhao et al have shown that in ovariectomized mice with consecutive estrogen related metabolic syndrome, changes of lumen diameters in common carotid artery, left ventricle ejection fraction and fractional shortening was significantly lower than in sham-operated group, but they registered higher common carotid artery thickness.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Large circulating EVs in MetS participate in enhanced SMC proliferation, migration, a proinflammatory profile, and activation of the ERK5/p38 pathway, leading to vascular inflammation and remodelling in AS. During inflammation, exosomes secreted by macrophage-transported microRNAs accelerate the development of AS ( Nguyen et al, 2018 ; Fitzsimons et al, 2020 ). In addition, exosomes from platelets, vessel cells ( He et al, 2018 ; Bai et al, 2020b ), inflammatory adipocytes ( Wadey et al, 2019 ) and dendritic cells increased the level of inflammatory factors and recruited inflammatory cells and promoted their adhesion to the vessel wall, leading to a chronic inflammatory response process in AS.…”
Section: Ev-circrnas In the Progression Of Asmentioning
confidence: 99%